Tailoring services / Holysteve Henry... [et al.] - Henry, Holysteve; Masulin, Jailani; Waheedah, Wafa; Samsuddin, Adiba; Wahanin, Siti Aidah (2015)
The name of our company is Kawaii Tailor and Co. Kawaii Tailor and Co is a business that provides sewing services. For example, wedding dress, formal clothes.and so on. Our business location is located in lot 24, 1st floor, 1 Borneo Hypermall, Kota Kinabalu, Sabah. Our business commencement was on 1 January 2015. We named our company as Kawaii Tailor and Co by agreement between the partners. We choose the word" Kawaii" because its means as the quality of lovable in the context of Japanese Culture. It has become a prominent aspect of Japanese popular culture, entertainment, clothing, food, toys, personal appearance, behavior, and mannerisms. Hence, we combined the word Kawaii with tailor to make our customer understands that our services will produce a lovable clothes for them. We choose this business because we can see there is a lot of opportunity in this field. Clothes are an everyday needs. This means that the demands for clothes will increase every day. Hence, our company will continuously provide our services to fulfill the needs of our customers.